Suspect’s access to a lawyer at an early stage of criminal proceedings in view the case-law of the European Court of Human Rights - Andrzej Sakowicz (Revista Brasileira de Direito Processual Penal, 2021)
Access to a lawyer at the pre-trial stage of proceedings is an essential component of the right to defense in criminal proceedings and the right to a fair trial. Access to a lawyer enables the accused to make a good decision for his her defence. At present, there is no doubt that prompt access to a lawyer constitutes an important counterweight to the vulnerability of suspects in police custody, ensures equality of arms and provides a fundamental safeguard against coercion. This study analyses a suspect’s right to access to a lawyer at the initial stage of criminal proceedings in the case law of the European Court of Human Rights. The first part of the article provides an analysis of the understanding of the right to a lawyer at the pre-trial stage as applied by the ECtHR prior to the Salduz case. This period in the ECtHR’s case law was characterized by a lack of precision as to the temporal limits of the right laid down in Article 6 § 3 (c) of the ECHR. The next part shows the changes brought about by the judgment in the Salduz case regarding the protection of suspects and ensuring their right to counsel. It is argued that the Salduz doctrine not only covered the suspect’s access to a lawyer at the initial stage of the pre-trial proceedings, but also stressed the obligation to inform the suspect of his or her rights, including the right to remain silent. An important element of the Salduz doctrine was the possibility to eliminate evidence obtained during an interrogation conducted at an early stage of the pre-trial proceedings in the absence of a defense counsel. Further, the paper argues that the standard set out in the judgment in the Salduz v. Turkey case was confirmed in a number of rulings. The fourth part of the paper draws attention to the erosion of the Salduz standard that occurred with the judgment in the Ibrahim and Others v. the UK case. The article also brings into focus recent judgments of the ECtHR which have reinforced the view expressed in the Ibrahim and Others v. the UK case concerning a test of fairness of a trial as whole. It is underlined in the conclusions that recent ECtHR’s case law does not provide any cause for optimism regarding legal assistance at an early stage of criminal proceedings.